RANCANG BANGUN PERMAINAN UNTUK MELATIH MOTORIK DAN PENGETAHUAN ANAK TERHADAP BUAH DAN SAYUR BERBASIS COMPUTER VISION - Istiqomah Sumadikarta; Fikhri Fadhilah (FAKULTAS TEKNIK, 2024)
With the advancement of current technological developments, it accelerates the development of various aspects of life, one of which is the development of education. Children at an early age need a way to help their learning process by playing to train their motor skills and knowledge about fruits and vegetables using educational games with Computer Vision technology. The creation of Educational Games to train children's motor skills and knowledge about fruits and vegetables based on computer vision is designed using python, PyCharm, OpenCV, Mediapipe, and PyGame. This research produces a multimedia application as a game-based learning environment for children. With this educational game, it is hoped that it can be an alternative game-based learning environment that can attract children's interest in learning by playing. Based on the results of functional testing, this educational game can run as it should. Based on the test results, this educational game based on Computer Vision technology can be played at a distance of 1 meter, 1.5 meters, and 2 meters so that the response from the hand can be properly detected by fruit and vegetable objects.